Seminal androgens, oestradiol and progesterone in oligoasthenoteratozoospermic men with varicocele. (15th August 2013) - Zalata, A.; El‐Mogy, M.; Abdel‐Khabir, A.; El‐Bayoumy, Y.; El‐Baz, M.; Mostafa, T.
Summary This study aimed to assess seminal androgens, oestradiol, progesterone levels in oligoasthenoteratozoospermic (OAT) men with varicocele (Vx). In all, 154 men with matched age and body mass index were investigated that were divided into healthy fertile controls (n = 35), OAT men with Vx (n = 55), OAT men without Vx (n = 64). They were subjected to assessment of semen parameters, seminal levels of testosterone (T), androstenedione (A), 5α‐androstane‐3 α, 17 β‐diol (3 α‐diol), oestradiol (E2), 17‐hydroxyprogesterone (17‐OHP) and progesterone (P). Seminal levels of T and A were significantly decreased where seminal levels of 3 α‐diol, E2, 17‐OHP, P were significantly higher in OAT men with/without Vx compared with fertile controls. Sperm count, sperm motility and sperm normal forms percentage demonstrated significant positive correlation with seminal T and A and significant negative correlation with seminal 3 α‐diol, E2, P. It is concluded that in fertile men, seminal T and A are significantly increased and seminal 3 α‐diol, E2, 17‐OHP, P are significantly decreased compared with infertile OAT men with/without Vx. Association of Vx demonstrated a nonsignificant influence on these hormonal levels in OAT cases. Sperm count, sperm motility and sperm normal forms demonstrated significant positive correlation with seminal T, A and significant negative correlation with seminal 3 α‐diol, E2, P.